PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Angelia Agustin; Herry Goenawan Soedarsa (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study aims to analyze the effect of profitability and company size on audit delay in property and real estate sector companies during the 2019-2021 period. Property and real estate companies listed on the IDX for the 2019-2021 period are the samples in this study. The method used in sampling using purposive sampling for samples that have been determined according to certain qualifications. Data for valuation and measurement variables are obtained from annual reports, such as published independent auditor reports, total assets, and net income which are included in the IDX data base. The analysis technique used is multiple linear regression analysis. The results of this study indicate that profitability and company size have a positive and significant influence on audit delay in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period.